Abdominal vacuum therapy is a component of DAMAGE CONTROL SURGERY tactics for combat trauma to the abdomen - S.A. Aslanyan; V.Ya. Bily; I.V. Sobko; M.M. Davidyuk (Medičnì Perspektivi, 2024)
The goal of the study was to improve the outcomes of surgical care and treatment for patients with combat-related abdominal injuries at different levels of medical support during combat operations by using abdominal vacuum therapy as a component of Damage Control Surgery tactics.  At the II level of combat medical support within the Damage Control Surgery tactics, abdominal vacuum therapy was applied to 75 wounded male combatants with a combat abdominal injury, aged 37.4±8.3 years (main group). The comparison group consisted of 87 wounded patients aged 37.5±10.2 years, operated on using Damage Control Surgery tactics with drainage of the abdominal cavity and suturing of the skin only. 40.0% of the wounded in the main group and 46.0% of the comparison group were admitted with signs of traumatic shock of various degrees. According to the AdTS scale, 78.7% of the wounded in the main group were admitted in a serious condition, 21.3% – in an extremely serious condition; in the comparison group, 74.7% were in severe condition, 25.3% were in extremely severe condition. In 57.3% of the wounded of the main group, abdominal vacuum therapy was carried out in the irrigation-flow mode. 24.0% used standard bandages for abdominal vacuum therapy, 76.0% used partially improvised ones. The level of negative pressure was set in the range of 40-125 mm Hg in constant mode. Intra-abdominal pressure was measured by a standard method (through the bladder) at admission and after surgery. The assessment of the state of the abdominal cavity in the I and III phases of Damage Control Surgery was carried out according to the Abdominal Cavity Index scale – an integral assessment expressed in points based on factors that can be assessed visually during surgery. The volume of surgical interventions in the 1st phase of the Damage Control Surgery tactic depended on the nature of the damage to the abdominal organs and the condition of the wounded. After the completion of Phase I of Damage Control Surgery tactics, all wounded were evacuated by road medical transport and medical helicopters to the next level of medical support, with abdominal vacuum therapy during evacuation in the main group and Damage Control Resuscitation measures. Under the effect of abdominal vacuum therapy, the reduction of intra-abdominal pressure in the main group was pronounced (Δ=9.2; p<0.01) than in the comparison group (Δ=6.1; p<0.01). Abdominal vacuum therapy during the II phase of the Damage Control Surgery tactic made it possible to clean the abdominal cavity better (p<0.0001) than in the comparison group and provided better preparation for the implementation of the III phase of this tactic. As a result, reliable protection from external factors, active prevention of intra-abdominal pressure and rehabilitation of the abdominal cavity during the application of abdominal vacuum therapy during the II phase of Damage Control Surgery tactics in the main group of wounded after obstructive resections of the small intestine in the I phase made it possible to completely abandon terminal stomas in the III phase (in the comparison group – 5) in favor of the formation of small bowel intestinal anastomoses, and during obstructive colon resections, the number of terminal colostomas in the main group was reduced to 50.0% (in the comparison group -90.9%, р=0.004), also in favor of the formation anastomoses, which significantly improved the functional results of providing assistance to the wounded with a combat abdominal injury. The use of abdominal vacuum therapy during phases I-II of the Damage Control Surgery (DCS) tactics allows for the optimization of the scope of surgical interventions in phase III of Damage Control Surgery and significantly improves the functional outcomes of surgical care and treatment for patients with combat abdominal injuries at various levels of medical support during combat operations.